La dialectique du rationnel et de l’effectif: une ontologie hégélienne pour changer le monde (Revista Eletrônica Estudos Hegelianos, 2023)
The different interpretations of Hegel’s controversial formula of the Preface of the Principles of the Philosophy of Right, declaring that “Was vernünftig ist, das ist wirklich; und was wirklich ist, das ist vernünftig”, correspond to the different readings of the overall orientation of the Hegelian notion of objective spirit in general and his political philosophy in particular. This could be illustrated by several examples such as the case of Rudolf Haym (1857) who famously considered the formula as the very expression of Hegel’s political conservatism, and the recently published interpretation by J.-F. Kervégan (2021), according to which we should read Hegel’s formula as an epistemological judgment and his entire political philosophy as epistemology. After a critical discussion of these two examples, I propose to distinguish between a formal and a speculative paradigm of interpretations, and I present, within the latter, an analysis of the dialectical relations between Hegel’s notions of effectiveness (Wirklichkeit) and rationality (Vernüftigkeit), so that the formula of the Preface would not only maintain the role of philosophy in changing the world, but also indicate new potentialities regarding the realization (Verwirklichung) of revolutionary political thought.